Physical and Sensory Quality of Broiler Meat as Influenced by Dietary Supplementation of Turmeric (Curcuma longa), Garlic (Allium sativum) and in Combinations as a Feed Additive - Purwanti, Sri; Zuprizal, Zuprizal; Yuwanta, Tri; Supadmo, Supadmo (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2018)
This research was conducted to evaluate the effect of turmeric water extract, garlic and combinations of turmeric and garlic as feed additives in broiler diets on the physical and sensory quality of broiler meat. During the study, the chicken were given 5 feeding treatments, i.e. R0 (basal ration without phytobiotic and antibiotics) , R1 (basal diet + 0.015% zinc bacitracin + 2.485% filler), R2 (basal ration + 2.50% TE), R4 Â (basal ration + 2.00% GE + 0.50% filler), and R5 (basal ration + 2.50% TGE). The base diet was composed of: yellow corn, meat and bone meal, poultry meat meal, soybean meal, oil, mineral mix, calcium carbonate, dicalcium phosphate, salt, L-lysine-HCl, and DL-methionine. Variables observed were physical quality (pH, water holding capacity, cooking lose, and tenderness) and sensory quality. Data regarding physical quality were statistically analyzed by one-way ANOVA followed by the orthogonal contrast for significant results, and data of sensory quality by non-parametric methods such as the Hedonic Kruskal-Wallis test. The results showed that the physical quality of meat had no effect (P>0.05), except the significant water holding capacity (P<0.05) which was lower with phytobiotic extract supplementation. All sensory test parameters in fresh and cooked meat had no effect (P>0.05) following phytobiotic extract supplementation, except for the color and acceptability (P <0.05) in fresh broiler meat. The conclusion of the research was that 2.5% TE, 2.0% GE and 2.5% TGE is capable of acting as a feed additive to increase the physical and sensory quality of broiler meat.